Analisis Implementasi Birokrasi Ideal Weber Pada Biro Sekretariat Pimpinan Sekretariat Jenderal Dewan Perwakilan Daerah - Isvandanu Wicaksono; Muhammad Prakoso Aji (Administratio, 2025)
This study analyzes the implementation of Max Weber's ideal bureaucracy in the Bureau of Headship within the Secretariat General of the Regional Representative Council (DPD) of the Republic of Indonesia. Weber defines ideal bureaucracy as an organizational system governed by five core principles: legal-rational authority, hierarchical structure, technical competence, impersonality, and a merit-based career system. This research adopts a qualitative approach, utilizing literature review, direct qualitative observation, and in-depth interviews with three informants: two civil servants from the DPD Secretariat (one an IPDN graduate, the other a non-IPDN official), and a governance scholar. The findings reveal that efficiency and rationality are generally well-applied through structured task distribution and formal procedures. However, patron-client relationships among IPDN alumni pose challenges to impersonality and meritocracy. To enhance the validity of the findings, data triangulation was conducted through cross-verification of interviews, field observations, and official bureaucratic documents. Strengthening reform through transparent recruitment, performance-based promotion, and institutional oversight is essential. With these measures, the Bureau of Headship has the potential to become a model of effective, accountable, and professional governance within Indonesia’s public sector.